2011
DOI: 10.1007/s10147-011-0268-5
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related bloodstream infection with removal of catheter in pediatric oncology patients: a 10-year experience in Taiwan

Abstract: Factors such as microbiological isolates, age of infection, the status of malignancy, and neutropenia are related to catheter outcome. The reduction in patients with positive cultures needing removal of the catheters can be related to improved nursing care and more aggressive antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…However, neutropenia was an important factor for catheter removal (Celebi et al, 2013), Neutropenia may be correlated with clinical severity of CLABSI. In the study by Chen, Yang, Jaing, Lai, and Hung (2012) CLABSI occurred especially during severe neutropenia. Our result is consistent with those of other studies that emphasize the significance of neutropenia following receipt of chemotherapy in patients with hematologic malignancies as a major risk factor for infection.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, neutropenia was an important factor for catheter removal (Celebi et al, 2013), Neutropenia may be correlated with clinical severity of CLABSI. In the study by Chen, Yang, Jaing, Lai, and Hung (2012) CLABSI occurred especially during severe neutropenia. Our result is consistent with those of other studies that emphasize the significance of neutropenia following receipt of chemotherapy in patients with hematologic malignancies as a major risk factor for infection.…”
Section: Discussionmentioning
confidence: 95%
“…The National Nosocomial Infections Surveillance System Pre-Report indicated that the rate of CLABSI was 6.0 per 1,000 catheter-days in pediatric intensive care units, but no data were available for the PHO unit (Ertek, Muezzinoglu, Kurtoglu, Arabacı, & Cetinkaya Sardan, 2010). CLABSI rates changed from 0 to 7.4 per 1,000 catheter-days in the PHO population (Abedin & Kapoor, 2008; Allen et al, 2008; Biwersi et al, 2009; Celebi et al, 2013; Chenet al, 2012; Fadoo et al, 2015; Hatakeyama et al, 2011; Langley et al, 2015; Matsuzaki et al, 2006; Newman et al, 2012; Pinon et al, 2009; Shen, Gao, Wang, Mao, & Wang, 2009; Simon et al, 2008; Tsai et al, 2015; Yazıcı et al, 2013; Zachariah et al, 2014). It is important to keep in mind that this is a sample of patients with hematological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hospitals, RGM may also be responsible for outbreaks of infections that originate from contaminated medical equipment and water 3 . However, RGM are considered a rare cause of CRBSIs 4‐6 . Herein, we report a patient of a myeloid leukemia associated with Down syndrome (ML‐DS) who developed a CRBSI caused by Mycobacterium chelonae .…”
Section: Introductionmentioning
confidence: 99%
“…reported that leukemia was an independent risk factor for CR‐BSI . The overall incidence density of CR‐BSI in pediatric malignancy was reported as 0.44 per 1000 catheter days, but there is a gap in the CR‐BSI rate between malignant disease and intestinal failure: there are no studies on the risk of CR‐BSI in pediatric patients with malignant disease and intestinal disorder at a single center …”
mentioning
confidence: 99%